2020
DOI: 10.1590/1676-0611-bn-2019-0874
|View full text |Cite
|
Sign up to set email alerts
|

Woody vegetation associated with rocky outcrops in Southern Amazonia: a starting point to unveil a unique flora

Abstract: Abstract: Vegetation associated with rocky outcrops is responsible for increasing floristic and landscape diversity, since its flora can be different from the adjacent landscape. Our objective was to characterize the woody vegetation associated with the rocky outcrop of the RPPN Mirante da Serra, Cristalino region, Mato Grosso State, Brazil. In a Deciduous Seasonal Forest associated with granite outcrops, we demarcated a plot of 1ha. We performed collections on this plot, installed for conducting monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(45 reference statements)
1
2
0
2
Order By: Relevance
“…Such bias is well documented for the Amazon flora (BFG 2015). However, Silva et al (2020), investigating woody species in the same study area as ours, also found a small number of species already assessed for threat (16 species already assessed and 102 not assessed). Thus, this seems to Biota Neotrop., 22(3): e20211313, 2022 http://dx.doi.org/10.1590/10.1590/1676-0611-BN-2021-1313 http://www.scielo.br/bn be a general gap -not only for the herbaceous stratum -in the threatened species assessment for the RPPN Mirante da Serra, and perhaps for the Amazon as a whole.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Such bias is well documented for the Amazon flora (BFG 2015). However, Silva et al (2020), investigating woody species in the same study area as ours, also found a small number of species already assessed for threat (16 species already assessed and 102 not assessed). Thus, this seems to Biota Neotrop., 22(3): e20211313, 2022 http://dx.doi.org/10.1590/10.1590/1676-0611-BN-2021-1313 http://www.scielo.br/bn be a general gap -not only for the herbaceous stratum -in the threatened species assessment for the RPPN Mirante da Serra, and perhaps for the Amazon as a whole.…”
Section: Discussionsupporting
confidence: 52%
“…In this sense, studies have highlighted the importance of expanding the sampling of vegetation in rock habitats in the south of the Amazon (Sasaki et al 2010, Zappi et al 2011. Based on this, samples of the woody component in Seasonal Deciduous Forest associated with rock outcrops in the Cristalino Region -focus of our study -have brought important contributions, such as the addition of species to the regional flora, expansion of species distribution areas, as well as discussions related to conservation status and endemism (Silva et al 2020). The Cristalino Region shelters different types of vegetation and varied physiognomies that reflect its geological and geomorphological complexity, and constitutes a key area for biodiversity conservation in the Brazilian Amazon (Zappi et al 2011, Maury et al 2004.…”
Section: Introductionmentioning
confidence: 84%
“…Fabaceae conta com diversos estudos realizados na região norte do Estado, pois inúmeras novidades taxonômicas e uma coleção referência da família se encontra no Herbário de acrônimo HERBAM (Lopes et al 2015;Fernandes et al 2015;Fernandes et al 2016a;Souza et al 2016;Silva et al 2019) Em relação a Thismiaceae e Bignoniaceae, estas são exemplos que inventários florísticos específicos e intensos, feitos por taxonomistas especialistas regionais podem mudar o panorama e padrões de riqueza florística documentada para Amazônia. Pois, a primeira nunca havia sido registrada em listas florísticas no Mato Grosso (Da Silva et al 2020). E a segunda, nunca apareceu em primeiro lugar em listas florísticas, cuja explicação deve-se aos extensos esforços de inventários focados especificamente para o grupo na região (Ribeiro 2018), especialidade do primeiro autor deste estudo.…”
Section: Resultsunclassified
“…;Petini- Benelli et al 2014;Petini-Benelli & Soares-Lopes 2015;Bortolan et al 2016;Fernandes et al 2015;Fernandes et al 2016;Souza et al 2016;Petini-Benelli & Soares-Lopes 2017;Petini-Benelli & Izzo 2017;Almeida 2018;Cardoso 2019;Ribeiro 2018;Silva et al 2019;Koch et al 2019;Da Silva et al 2020;Ribeiro et al 2020;Silva et al 2020;Ribeiro et al 2021). Checklist das plantas vasculares (Angiospermas) no município de Nova Bandeirantes, MT.…”
unclassified
“…The thicker palisade parenchyma and higher stomatal and trichome density (PPT, STD and TRIAD, respectively) we verified in the leaves of Deciduous Forest may be interpreted as typical changes of sun plants (i.e., plants under higher luminosity conditions). This forest is located in a rocky outcrop and showed significant greater canopy openness due to the sparse distribution of woody plants (Silva et al 2020). Along with this, at the time of leaf sampling for anatomical measurements (rainy-dry transition season), woody plants of the Deciduous Forest start to shedding leaves (Sasaki et al 2010;E.…”
Section: Discussionmentioning
confidence: 99%